Theoretical foundations of the hypotheses of material effort - BURZYŃSKI, Włodzimierz (Engineering Transactions, 2008)
Translated from the original paper in Polish (“Teoretyczne podstawy hipotez wytężenia”, Czasopismo Techniczne, 1929, 47, 1–41, Lwów) by Anna Stręk; scientific editor Ryszard B. Pęcherski